Circumferential Material Flow in the Hydroforming of Overlapping Blanks - Cong Han; Hao Feng (Metals, 2020)
The hydroforming of the overlapping blanks is a forming process where overlapping tubular blanks are used instead of tubes to enhance the forming limit and improve the thickness distribution. A distinguishing characteristic of the hydroforming of overlapping blanks is that the material can flow along the circumferential direction easily. In this research, the circumferential material flow was investigated using overlapping blanks with axial constraints to study the circumferential material flow in the hydroforming of a variable-diameter part. AISI 304 stainless steel blanks were selected for numerical simulation and experimental research. The circumferential material flow distribution was obtained from the profile at the edge of the overlap. The peak value located at the middle cross-section. In addition, the circumferential material flow could be also reflected in the variation of the overlap angle. The variation of the overlap angle kept increasing as the initial overlap angle increased but the improvement of the thickness distribution did not. There was an optimal initial overlap angle to minimize the thinning ratio. An optimal thickness distribution was obtained when the initial angle was 120° for the hydroforming of the variable-diameter part with an expansion of 31.6%.